Data Security Analysis on the Use of E-Commerce to Prevent Online Fraud - Yusnanto, Tri; Fatkhurrochman, Fatkhurrochman; Muin, Muhammad Abdul; Mustofa, Khaoirul (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
As the purchasing and selling process has changed, so too has electronic fraud, which has led to several individuals losing money to online frauds. The goal of this study is to ascertain how trust affects the high rate of e-commerce fraud when executing transactions. Qualitative interpretative methodologies are used in this investigation. Research that looks at phenomena having meaningful patterns and relationships is known as phenomenological research. Field research indicates that a lack of understanding, ignorance, the temptation of phony gifts, high unemployment and poverty rates, and weak government security measures are the main causes of fraud in e-commerce transactions. about the various forms of fraud that occur in online transactions.